EFFECT OF DIFFERENT CONCENTRATION CINNAMON EXTRACTS (CINNAMOMUM BURMANNII) IN GROWTH LACTOBACILLUS ACIDOPHILUS (IN VITRO) - Sherlin Mentary Farizha; Desy Armalina; Diah Ajeng Purbaningrum (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background: One of the dental and oral health problem that really need attention is caries. Lactobacillus acidophilus is one of the bacteria that play a role in the process of further caries in dentin. We can control it by using materials like antibacterial. Cinnamon barks (Cinnamomum burmannii) is a plant from Indonesia that contains antibacterial compounds such as sinamaldehid, flavonoid, tannins, alkaloids, and saponinsPurpose: To know the effect of various concentrations of cinnamon barks extracts (Cinamomum burmannii) on the growth of Lactobacillus acidophilus in vitroMethod: True experimental study with the post test control group design has 25 samples. Cinnamon barks was extracted by the soxhletation method then phytochemical tests were performed to determine the antibacterial compounds. Antibacterial tested using the diffusion method to determine the diameter of the inhibitory zone. Statistical tests using Kruskal-Wallis and Man-WhitneyResult: The mean inhibition zone diameters at concentrations of 6.25%, 12.5%, 25%, 50%, and positive controls were 4.80 mm, 10.99 mm, 16.83 mm, 19.14 mm, 29, 80 mm. Kruskal Wallis test showed significant differences in inhibition zone diameter in inhibiting the growth of Lactobacillus acidophilus p = 0,000321 (p <0.05). The Man Whitnney test showed a significant difference between the concentration of 6.25% with concentrations of 25% and 50% and concentrations of 12.5% with concentrations of 25% and 50%. There were no significant differences between the concentrations of 6.25% with 12.5% and 25 % with 50%Conclusion: There is an effect of cinnamon bark extracts from various concentrations on the growth of Lactobacillus acidophillus as assessed by the formation of inhibition zone diameters. The 25% concentration is the minimum concentration that can significantly inhibit bacteria